Functional outcome in patient with giant cell tumour distal radius after reconstruction by en-bloc resection and non-vascularized fibular bone graft: a case report - Yudha, Gede Agung Krisna; Wiratnaya, I. Gede Eka; ., Dwiwahyonokusuma; Putra, I. Gede Mahardika (International Journal of Research in Medical Sciences, 2020)
Giant cell tumor (GCT) is a relatively common benign primary bone tumor, commonly seen in end of long bones. Treatment goals for GCT of the distal radius are complete excision of the tumor and preservation of wrist function. Usually it can be treated by en-bloc resection and reconstruction using autogenous non vascularized ipsilateral proximal fibular graft. Authors present a case of twenty two years old female complaining of pain and lump in left wrist since two years ago. The pain worsened since 1 month before consultation, but did not radiate elsewhere. Pain was aggravated by movement and decreased with rest. Physical examination revealed a 3 cm mass with tenderness over left wrist. With clinical suspicion of benign bone tumor on left wrist, further evaluation was needed. Plain radiograph revealed an expansile, lytic lesion and soap bubble appearance on her left distal radius like a GCT. Open biopsy result revealed similar morphology with GCT. Reconstruction by en-bloc surgical excision, followed with non-vascularized fibular bone graft fixed with dynamic compression plate (DCP) and wrist ligament reconstruction and fixation of the head of the fibula with carpal bones and distal end of the ulna using K-wires along with palmaris longus tendon were performed. En-bloc resection of giant cell tumors of the lower end radius is a widely accepted method. Reconstruction with non-vascularized fibular graft, internal fixation with DCP with trans fixation of the fibular head and wrist ligament reconstruction minimizes the problem and gives satisfactory functional results.